CRISP-SET QUALITATIVE COMPARATIVE ANALYSIS (CSQCA): KONFIGURASI KONDISI YANG BERPENGARUH TERHADAP KEMAMPUAN BERPIKIR REFLEKTIF MATEMATIKA SISWA - Otong Suhyanto; Muhammad Hijri Haydar (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
CS-QCA is based on set theory, but its use in research in the field of mathematics is not much. The cs-QCA method dichotomizes independent variables (in QCA they are called conditions) and outcomes to be two: true [1] to declare full membership, and false [0] for non-membership. This study aims to find the configuration of conditions that affect the ability to think mathematically reflective. The research was conducted at SMA Negeri 8 Tangerang Selatan in the Odd Semester of the 2022/2023 Academic Year. The results of the analysis conclude that high mathematical reflective abilities can be obtained from a combination of high learning environment conditions and high learning resources and high experience and high economics, or it can also be obtained from high interest and learning environment and high learning resources and experience. high, or high interest and high learning environment and low learning resources and low experience and high economics, or high interest and low learning environment and high learning resources and low learning experience and high economics.